Role of mitochondria-associated endoplasmic reticulum membranes in insulin sensitivity, energy metabolism, and contraction of skeletal muscle - Nieblas, Bianca; Pérez-Treviño, Perla; García, Noemí (Frontiers in Molecular Biosciences, 2022)
Skeletal muscle has a critical role in the regulation of the energy balance of the organism, particularly as the principal tissue responsible for insulin-stimulated glucose disposal and as the major site of peripheral insulin resistance (IR), which has been related to accumulation of lipid intermediates, reduced oxidative capacity of mitochondria and endoplasmic reticulum (ER) stress. These organelles form contact sites, known as mitochondria-associated ER membranes (MAMs). This interconnection seems to be involved in various cellular processes, including Ca2+ transport and energy metabolism; therefore, MAMs could play an important role in maintaining cellular homeostasis. Evidence suggests that alterations in MAMs may contribute to IR. However, the evidence does not refer to a specific subcellular location, which is of interest due to the fact that skeletal muscle is constituted by oxidative and glycolytic fibers as well as different mitochondrial populations that appear to respond differently to stimuli and pathological conditions. In this review, we show the available evidence of possible differential responses in the formation of MAMs in skeletal muscle as well as its role in insulin signaling and the beneficial effect it could have in the regulation of energetic metabolism and muscular contraction.